Desain Aksesibilitas Penyandang Tuna Daksa dan Tuna Netra di Kawasan Wisata Hutan Bakau Denpasar Selatan - DHARMADIATMIKA , I MADE AGUS; GUNADI , I GUSTI ALIT; KOHDRATA , NANIEK (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2012)
ABSTRACT Accessibility Design for Handicapped in Mangrove Reserve Recreation Area in Denpasar The research on designing accessibility for handicapped people in an outdoor recreation facility, specifically in mangrove reserve area, was done due to the authors concern in the lack of handicapped friendly public facilities in Indonesia. The choice on a natural setting site of mangrove reserve area is based on two reasons. First is to prove that design and creativity are able to create an accessible outdoor recreation facility for handicapped users. Second, improvements on handicapped facilities can be done without compromising the nature. The handicapped users access to recreation facilities are designed to give the maximum opportunities for users to interact with nature and receive information as well. Some facilities design may require assistance from others in order to make sure safety for handicapped users. Nonetheless, this research has offered ideas and alternatives of outdoor recreation facilities design for handicapped. Keywords: handicapped facilities, design for handicapped